2020
DOI: 10.1002/cctc.202000320
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of Naringinase over Two‐Dimensional 2D Zeolites and its Applications in a Continuous Process to Produce Citrus Flavonoids and for Debittering of Juices

Abstract: The crude naringinase from Penicillium decumbens and a purified naringinase with high α‐L‐rhamnosidase activity could be covalently immobilized on two‐dimensional zeolite ITQ‐2 after surface modification with glutaraldehyde. The influence of pH and temperature on the enzyme activity (in free and immobilized forms) as well as the thermal stability were determined using the specific substrate: p‐nitrophenyl‐alpha‐L‐rhamnopyranoside (Rha‐pNP). The crude and purified naringinase supported on ITQ‐2 were applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…The catalytic benefits of these highly accessible delaminated materials have been demonstrated in very diverse fields, including petrochemistry (i.e., cracking, hydrocracking, and aromatic alkylation), fine-chemistry (i.e., olefin epoxidation, synthesis of acetals, Beckman rearrangement, and synthesis of diamino diphenylmethane (DADPM)) or biomass transformations (i.e., syntheses of alkyl 5-benzyl-2-furoates, and xylenes), as will be discussed in other sections of this Account. , Interestingly, the large exposed external surface area in these delaminated 2D zeolites has permitted their functionalization with enzymes, allowing the design of very interesting materials combining the benefits of both heterogeneous and enzymatic catalysts. …”
Section: Synthesis Of Micro- and Mesoporous Materialsmentioning
confidence: 99%
“…The catalytic benefits of these highly accessible delaminated materials have been demonstrated in very diverse fields, including petrochemistry (i.e., cracking, hydrocracking, and aromatic alkylation), fine-chemistry (i.e., olefin epoxidation, synthesis of acetals, Beckman rearrangement, and synthesis of diamino diphenylmethane (DADPM)) or biomass transformations (i.e., syntheses of alkyl 5-benzyl-2-furoates, and xylenes), as will be discussed in other sections of this Account. , Interestingly, the large exposed external surface area in these delaminated 2D zeolites has permitted their functionalization with enzymes, allowing the design of very interesting materials combining the benefits of both heterogeneous and enzymatic catalysts. …”
Section: Synthesis Of Micro- and Mesoporous Materialsmentioning
confidence: 99%
“…Recently, we have reported that the pure silica 2D ITQ-2 zeolite is an excellent carrier to support enzymes such as naringinase [ 33 ] and alcohol dehydrogenases [ 34 ] that have been used efficiently, in both batch and flow mode, in the production of citrus flavonoids as well in the production of chiral alcohols from racemic mixtures through a chemo-enzymatic cascade process respectively. The ITQ-2 zeolite that can be prepared by a dual-templating one-step synthesis or by the delamination of a layered Mobil twenty two (MWW) zeolite precursor [ 35–38 ] is a 2D system of 2.5-nm-thick thin sheets.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bitterness cannot be completely removed by ultrafiltration (Loizzo et al, 2019). In recent years, adding the enzyme naringinase in orange juice processing has become a common practice for the removal of naringin from fruit juice (Carceller et al, 2020), due to its specific hydrolysis of the substrates (Borzova et al, 2018;Zhu et al, 2017).…”
mentioning
confidence: 99%